Analisis Faktor Risiko yang Berhubungan dengan Kejadian Low Back Pain (LBP) pada Lansia di Panti Sosial Tresna Werdha Budi Mulia 1 - Khusniyatul Khasanah; Ricky Riyanto Iksan (Jurnal Kesehatan Amanah, 2025)
Low Back Pain (LBP) is a pain in the lower back that can occur as a result of repetitive activities and aging. factors that can cause LBP are individual factors, occupational factors and environmental factors, individual factors in the form of age, gender, Body Mass Index (BMI), educational history, smoking habits, work activities, and history of trauma. Work factors are work attitude, working period, length of work, workload. While environmental factors are psychology, mental factors and work stress. The purpose of this study is to analyze risk factors related to the incidence of Low Back Pain (LBP) in the elderly at the Tresna Werdha Budi Mulia 1 Social Home. Method this study is a quantitative research using a cross sectional approach research design. The sample taken with the slovin formula was obtained by 154 respondents. Data collection will be carried out in July 2024 by filling out questionnaires. The data analysis consisted of univariate analysis and bivariate analysis using Chi-Square. Results the risk factor associated with the incidence of LBP is age with a p value 0.05), sports activity with a p value of 0.307 (>0.05), and a history of disease with a p value of 0.057 (>0.05). Conclusion the results of the analysis show that the age factor has a significant influence on the incidence of LBP in the elderly. The importance of interventions aimed at reducing risk through prevention and health management programs tailored to the specific needs of the elderly population in these social homes.